TRADE MILITER RELATIONS BETWEEN RUSSIA AND NORTH KOREA ACCORDING TO CONSTRUCTIVISM : RUSSIA’S INVOLVEMENT IN NUCLEAR AND PANMUNJOM DECLARATION - Dwi Warda Cahya Kamila (Universitas Budi Luhur, 2026)
Abstract: Political conditions on the Korean peninsula are always an interesting topic to discuss, the involvement of superpower countries since the Korean War is also an important topic, one of which is military cooperation between North Korea and Russia which has existed since the 1953 Korean War. Using Constructivist theory, this article analyses North Korea-Russia military-trade cooperation beyond material power, examining how shared historical identities and opposition to Western hegemony shape their alignment. It evaluates Russia’s involvement in North Korea’s nuclear development and assesses whether Pyongyang's missile tests violate the 2018 Panmunjom Declaration. Methodologically, this study employs a qualitative descriptive approach with an explanatory analysis technique. The findings reveal that their contemporary partnership has evolved from historical ideological affinity into a strategic alliance driven by mutual isolation under Western sanctions. Furthermore, North Korea has de facto violated the Panmunjom Declaration, as its deeply socialized Songun (military-first) identity consistently overrides its denuclearization commitments. Abstrak: Kondisi politik di semenanjung Korea selalu menjadi topik menarik untuk dibahas, keterlibatan negara-negara adikuasa sejak Perang Korea juga merupakan topik penting, salah satunya adalah kerja sama militer antara Korea Utara dan Rusia yang telah ada sejak Perang Korea 1953. Menggunakan teori Konstruktivis, artikel ini menganalisis kerja sama militer, perdagangan antara Korea Utara dan Rusia di luar kekuatan material, dengan memeriksa bagaimana identitas sejarah yang sama dan penolakan terhadap hegemoni Barat membentuk keselarasan mereka. Ini mengevaluasi keterlibatan Rusia dalam pengembangan nuklir Korea Utara dan menilai apakah uji coba rudal Pyongyang melanggar Deklarasi Panmunjom 2018. Secara metodologis, studi ini menggunakan pendekatan deskriptif kualitatif dengan teknik analisis eksplanatori. Temuan menunjukkan bahwa kemitraan kontemporer mereka telah berkembang dari afinitas ideologis historis menjadi aliansi strategis yang didorong oleh isolasi timbal balik di bawah sanksi Barat. Selain itu, Korea Utara secara de facto telah melanggar Deklarasi Panmunjom, karena identitas Songun (militer-pertama) yang sangat terinternalisasi secara konsisten mengesampingkan komitmennya untuk denuklirisasi.